2016
DOI: 10.3389/fnhum.2016.00614
|View full text |Cite
|
Sign up to set email alerts
|

The Neuronal Correlates of Indeterminate Sentence Comprehension: An fMRI Study

Abstract: Sentences such as The author started the book are indeterminate because they do not make explicit what the subject (the author) started doing with the object (the book). In principle, indeterminate sentences allow for an infinite number of interpretations. One theory, however, assumes that these sentences are resolved by semantic coercion, a linguistic process that forces the noun book to be interpreted as an activity (e.g., writing the book) or by a process that interpolates this activity information in the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 78 publications
1
16
0
Order By: Relevance
“…The role of the right inferior frontal lobe in sentence comprehension has also been shown previously, particularly for older compared to younger neurologically normal participants ( Wingfield and Grossman, 2006 ), when words are ambiguous ( Mason and Just, 2007 ), when sentences are reversible ( Meltzer et al , 2010 ) or indeterminate ( de Almeida et al , 2016 ), and when patients with aphasia after left hemisphere strokes are recovering their sentence comprehension abilities ( van Oers et al , 2010 ; Mohr et al , 2014 ; Kielar et al , 2016 ). Finally, implication that the right hemisphere may be playing a non-linguistic executive role in normal speech comprehension has also been proposed ( Bozic et al , 2010 ; Vigneau et al , 2011 ; Baumgaertner et al , 2013 ).…”
Section: Discussionsupporting
confidence: 63%
“…The role of the right inferior frontal lobe in sentence comprehension has also been shown previously, particularly for older compared to younger neurologically normal participants ( Wingfield and Grossman, 2006 ), when words are ambiguous ( Mason and Just, 2007 ), when sentences are reversible ( Meltzer et al , 2010 ) or indeterminate ( de Almeida et al , 2016 ), and when patients with aphasia after left hemisphere strokes are recovering their sentence comprehension abilities ( van Oers et al , 2010 ; Mohr et al , 2014 ; Kielar et al , 2016 ). Finally, implication that the right hemisphere may be playing a non-linguistic executive role in normal speech comprehension has also been proposed ( Bozic et al , 2010 ; Vigneau et al , 2011 ; Baumgaertner et al , 2013 ).…”
Section: Discussionsupporting
confidence: 63%
“…While it is clear that Lisa began doing something with a book, the sentence is indeterminate with regards to what exactly Lisa began doing. This kind of construction has been the object of investigation in theoretical linguistics (Pustejovsky, 1995(Pustejovsky, , 2011de Almeida and Dwivedi, 2008;de Almeida and Riven, 2012;Asher, 2015; see also de Swart, 2011, for review), psycholinguistics (e.g., McElree et al, 2001;Traxler et al, 2002;de Almeida, 2004), and neuroimaging (Pylkkänen and McElree, 2007;Husband et al, 2011;de Almeida et al, 2016). What motivates general interest in indeterminate sentences is that, although they are grammatical and semantically felicitous -for a truth value judgment can be made -they appear to convey more information than what is explicitly said.…”
Section: Introductionmentioning
confidence: 99%
“…This enrichment process has since been the object of considerable experimental investigation involving numerous techniques such as self-paced reading (McElree et al, 2001;de Almeida, 2004), eye-tracking (Traxler et al, 2002(Traxler et al, , 2005Pickering et al, 2005;McElree et al, 2006a;Frisson and McElree, 2008;Katsika et al, 2012;Zarcone et al, 2014;Antal and de Almeida, 2020), probe recognition (Zarcone et al, 2014), sensibility judgments (McElree et al, 2006b), event-related potentials (ERPs; Baggio et al, 2010;Kuperberg et al, 2010), fMRI (Husband et al, 2011;de Almeida et al, 2016), magnetoencephalography (MEG; Pylkkänen and McElree, 2007), and aphasia (Piñango and Zurif, 2001). The majority of these studies have shown that indeterminate sentences engender processing delays or different activation patterns relative to various types of control sentences.…”
Section: Introductionmentioning
confidence: 99%
“…More generally, this region has been involved in semantic maintenance and cognitive control ( Shivde and Thompson-Schill 2004 ; Gajardo-Vidal et al. 2018 ), activating when processing an indeterminate sentence which can be interpreted in many different ways ( de Almeida et al. 2016 ) or when encountering a word with multiple meanings in a spoken sentence ( Rodd et al.…”
Section: Discussionmentioning
confidence: 99%